2010
DOI: 10.1179/cmq.2010.49.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Thermodynamic Properties of the Al-Mg Binary System Between 973-1073 K by the EMF Method

Abstract: The thermodynamic properties of an Al-Mg binary system with 0.07 to 12.10 at% Mg were determined at temperatures between 973-1073 K. The following Mg concentration cell was used: Mg (pure), MgCl 2 -CaCl 2 (eutectic), Al-Mg (melt). In this system, Mg shows negative deviation from Raoult's law. Alloys between 0 to 6 at% Mg obey Henry's law. The Henrian coefficient of Mg was 0.47, 0.52 and 0.53 at 973, 1023 and 1073 K, respectively. The EMF values were used for calculating the partial and integral Gibbs free ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Eth(±0.026) = 2.7728 + 0.09653logaMg [13] In a similar study, Aghdam and Soltanieh ( 25 The results in this study compares with the activity of Mg in molten Al-Mg alloys reported earlier (1,25). However, as proposed in our earlier study (1), it is quite likely that the measured emf is affected by the relatively large electron-hole transport in the solid electrolyte and the large difference in chemical potential of Mg at the two electrodes leading to polarisation of the solid-state reference electrodes.…”
Section: Table 1 Capacitance Values and Their Possible Interpretationsupporting
confidence: 80%
See 1 more Smart Citation
“…Eth(±0.026) = 2.7728 + 0.09653logaMg [13] In a similar study, Aghdam and Soltanieh ( 25 The results in this study compares with the activity of Mg in molten Al-Mg alloys reported earlier (1,25). However, as proposed in our earlier study (1), it is quite likely that the measured emf is affected by the relatively large electron-hole transport in the solid electrolyte and the large difference in chemical potential of Mg at the two electrodes leading to polarisation of the solid-state reference electrodes.…”
Section: Table 1 Capacitance Values and Their Possible Interpretationsupporting
confidence: 80%
“…Fig.9(a) shows the compared theoretical and measured emf, whereas, the average transport number is shown in Fig.9(b). On the average however, the measured emf values are lower by ~0.359±0.022 V(1,25). The transport number, tMg2+ for Mg 2+ -cations in MgHf4P6O24 solid electrolyte at 700±5 o C over the range of chemical potential at the two electrodes can be calculated using the difference between experimental and theoretical emfs assuming that the electrodes are not polarised.…”
mentioning
confidence: 98%
“…It was reported that the TGA curve shows progressive mass loss of the dried xerogel powders in the range from 30 to 500 °C and stabilisation between 750 and 870 °C. The mass loss from 99.9% to 62…”
Section: Resultsmentioning
confidence: 99%
“…The results in this study however compares favourably with the activity of Mg in liquid Al reported by Aghdam and Soltanieh. 62 However, it is quite likely that the measured emf is affected by the relatively large electron-hole transport in the electrolyte and the large difference in chemical potential of Mg at the two electrodes leading to polarisation of the solid reference electrodes. Hence, the testing of MgZr 4 P 6 O 24 solid electrolyte with other reference electrodes with higher Mg chemical potential is recommended.…”
Section: [ ] =mentioning
confidence: 99%
“…Eth(±0.026)/V = 2.7728 + 0.09653logaMg (13) Aghdam and Soltanieh [21] measured the activity of Mg in molten Al using electrochemical cell with the eutectic mixture of MgCl2-CaCl2 as an electrolyte in a temperature range from 700 to 800 o C and Mg composition from 0.07 to 12.1. The activity coefficient of Mg at 700 o C for dilute alloys up to 1.4 atom % Mg can be expressed by the relation, logγMg = -0.7624 + 23.183XMg (14) Expressing the activity of Mg in Eq.…”
Section: Transport Number Of Mg 2+ -Cation In Mghf4p6o24 Solid-state mentioning
confidence: 99%